The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/capr.12507
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists’ psychological well‐being: The role of epistemic orientation and emotion regulation

Abstract: Psychotherapists’ mental health has been traditionally associated with the harmful consequences of clinical practice. In contrast to this dominant model, a growing body of research in positive psychology has sparked an interest in therapists’ positive well‐being. The main objective of this study was to examine the relations between therapists’ epistemic orientation modes, emotion regulation strategies and psychological well‐being (PWB). This was a cross‐sectional study in which participants were 674 therapists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Despite in their meta-analysis Baldwin and Imel (2013) found that therapist effects accounted for only 3% of the variability in client outcome, Johns et al (2019) reported higher evidence of the therapist's role in the clients' outcomes, with effect sizes ranging from 8% to 17%. Among the more studied therapist's characteristics there are attachment style (Heinonen & Nissen-Lie, 2020), personality (Delgadillo et al, 2020), empathy (Elliott et al, 2018), reflective functioning (Reading et al, 2019), well-being (Palma & Gondim, 2021), and defense mechanisms (Vaillant, 2020). Therefore, the intent of this systematic review is not to demonstrate that integrity is the only variable involved in achieving therapeutic objectives but to highlight that Key Practitioner Message it is also an important dimension, able to interact with other unspecific factors in influencing the outcome.…”
Section: Integrity In Individual and Group Psychotherapy Researchmentioning
confidence: 99%
“…Despite in their meta-analysis Baldwin and Imel (2013) found that therapist effects accounted for only 3% of the variability in client outcome, Johns et al (2019) reported higher evidence of the therapist's role in the clients' outcomes, with effect sizes ranging from 8% to 17%. Among the more studied therapist's characteristics there are attachment style (Heinonen & Nissen-Lie, 2020), personality (Delgadillo et al, 2020), empathy (Elliott et al, 2018), reflective functioning (Reading et al, 2019), well-being (Palma & Gondim, 2021), and defense mechanisms (Vaillant, 2020). Therefore, the intent of this systematic review is not to demonstrate that integrity is the only variable involved in achieving therapeutic objectives but to highlight that Key Practitioner Message it is also an important dimension, able to interact with other unspecific factors in influencing the outcome.…”
Section: Integrity In Individual and Group Psychotherapy Researchmentioning
confidence: 99%
“…PL, in turn, comprises a sense of direction and pursuing personally meaningful goals (Ryff, 2018). Both dimensions have been empirically related to positive mental health outcomes (Palma & Gondim, 2021; Ryff, 2018). In the COVID‐19 context, for instance, Mirabito and Verhaeghen (2022) found that an online mindfulness‐based intervention with college students was associated with lower psychological distress and higher environmental mastery.…”
Section: Introductionmentioning
confidence: 99%